Larval morphology of benthic and interstitial water mites (Acari: Hydrachnidia) from a Luxembourgian stream - Martin, Peter (Zootaxa, 2016)
During a project of the Luxembourg National Museum of Natural History the parasitism of water mites dwelling a small stream (Lurenzgriecht) in the southern part of the country (Gutland) was investigated. The first step of the project was to clarify the taxonomy of the larvae of all stream-dwelling species. For that reason emergence traps were installed in the stream during 2002 and emptied every 14 days to obtain parasitized hosts. Additionally, rearing experiments were implemented in the laboratory to produce larvae of well-defined species/mothers but only with partly success. The stream has a well-known water mite inventory of 22 species, almost equally composed of true benthic species and species strongly adapted to hyporheic interstitial. The larvae of five species (Torrenticola elliptica, Atractides pumilus, Feltria motasi, Ljania macilenta, Neoacarus hibernicus) were described here as new to science. Due to the poor quality and availability of former descriptions a re-description was made for another species living in the stream (Sperchon denticulatus-gr.) and, additionally, for Hygrobates fluviatilis, a common stream-dwelling species of the area. The larvae of nine species of the Lurenzgriecht had already been sufficiently described for identification purposes (Protzia eximia, Sperchonopsis verrucosa, Sperchon clupeifer, S. thienemanni, Lebertia glabra, Atractides fonticolus, Feltria rouxi, Ljania bipapillata, Aturus fontinalis). The larvae of some other species (Aturus crinitus, Kongsbergia spp., Stygohydracarus subterraneus, Arrenurus haplurus) could neither be reared in the lab nor attributed to species for taxonomic reasons. With the exception of Kongsbergia spp. (no known larva of the genus worldwide) and Aturus crinitus (a rare species in the Lurenzgriecht) an identification key was compiled for the larvae of all known species of the stream using the new descriptions and all available information on the other ones.